Effect of Soil Conservation on Soil Erosion and Plant Performance under Pine–Durian Agroforestry Systems in Perhutani Production Forest - Arif Firmansyah; Kurniawan Sigit Wicaksono; Cahyo Prayogo; Didik Suprayogo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Logging activities in pine production forests create open land that increases surface runoff and soil erosion, highlighting the need for soil conservation during the early stages of agroforestry development. This study evaluated the effectiveness of mechanical and vegetative conservation practices, including biogeotextiles, in reducing runoff and erosion and improving plant growth and farm profitability in an early-stage pine–durian agroforestry system. A randomized factorial block design with two factors and a non-factorial control was applied. Mechanical conservation treatments included no terraces, ridge terraces, and bench terraces, while vegetative conservation treatments consisted of chili monoculture, peanut monoculture, chili–peanut intercropping, and intercropping combined with biogeotextiles. Results showed that mechanical conservation significantly reduced runoff and erosion, with bench terraces providing the greatest reductions (33–53% runoff; 48–75% erosion), followed by ridge terraces. Biogeotextiles further reduced erosion by up to 68%, although they increased implementation costs. Pine and durian growth were not significantly affected, whereas chili productivity increased under intercropping and terraced systems. Economically, bench terraces produced the highest profitability (R/C >6). Overall, integrating mechanical and vegetative conservation effectively improved hydro-logical function, crop productivity, and farm income in pine–durian agroforestry systems.